Development of Health Promotion through Video Media to Increase Knowledge of Bullying Prevention in Adolescents - Liyanovitasari Liyanovitasari; Puji Lestari; M. Imron Rosyidi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Indonesia ranks fifth with the highest bullying cases, which is 41.1% of 78 countries. The negative effects that occur on the victim are experiencing psychological disorders, including low self-esteem. Therefore, there is a need for health education related to bullying through video media. This media is effective because it is able to attract attention through real visualizations and audio that supports the content of the material. The purpose of this study is to find out the difference in students' knowledge before and after the provision of health education through video media. This research method uses the Quasy experimental pre posttest one group design method. The population in this study is all students of SMK NU Ungaran aged 15-18 years, in March 2024 a total of 820 students. The technique used for sampling in this study is Proportionate random sampling. The sample in this study is 92 students. This research instrument used a bullying knowledge questionnaire consisting of 15 statements with a choice of true, wrong answers and low, medium, and high knowledge measurement results. Of the 15 statements in this knowledge questionnaire, validity has been tested and declared valid all with a value range of 0.576-0.904. The results of the reliability test are 0.874. Bivariate analysis used a simple t test dependent test. The results of the study were obtained Most of the students' knowledge before the intervention was low category as many as 52 respondents (56.5%), while the knowledge after the intervention was mostly in the high category of 55 respondents (59.8%). The results of the dependent t-test were obtained with a p-value of 0.000 which proves that there is a difference in knowledge before and after health education through video media.